PENGARUH PENDEKATAN DISCOVERY LEARNING DAN MEDIA AUDIOVISUAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Fatia Fatimah; Desfitri Surya Ningsih; Jamaris Jamna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Discovery Learning approach assisted by audiovisual media on the mathematics learning outcomes of fourth-grade students at SDN 05 Kampung Jawa, Solok City. This research employed a quantitative method with a quasi-experimental design. The sample consisted of two classes, namely an experimental class and a control class, each comprising 25 students. The research instrument was a learning outcomes test that had been validated and tested for reliability. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing with an independent t-test. The results of the normality test indicated that the pretest and posttest data in both classes were normally distributed, while the homogeneity test showed that the variances of the two classes were homogeneous (Sig. > 0.05). The findings revealed that the average pretest score in the experimental class increased from 65.6 to 87.5 in the posttest, representing an improvement of 21.9 points. Meanwhile, the control class showed an increase from 71.0 to 76.4, with a difference of 5.4 points. The t-test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating that there is a significant effect of the Discovery Learning approach assisted by audiovisual media on students’ mathematics learning outcomes. It can be concluded that the implementation of the Discovery Learning approach supported by audiovisual media is effective in improving the mathematics learning outcomes of fourth-grade students at SDN 05 Kampung Jawa, Solok City. This learning model can be used as an alternative instructional strategy to create a more active, engaging, and meaningful learning process.